2010
DOI: 10.1177/147323001003800324
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Cytochrome P450 and Glutathione S-transferase Associated with Antituberculosis Drug-induced Hepatotoxicity in Chinese Tuberculosis Patients

Abstract: This study was designed to investigate the association of genetic polymorphisms of cytochrome P450 subtype 2E1 (CYP2E1) and glutathione S-transferase mu 1 (GSTM1) with susceptibility to antituberculosis drug-induced hepatotoxicity (ADIH) in Chinese tuberculosis patients. All patients were treated with a combination of isoniazid, rifampicin, pyrazinamide and ethambutol. Genomic DNA from 104 patients with ADIH and 111 without ADIH was analysed for the frequency of CYP2E1 RsaI and GSTM1 RsaI genotypes by polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 18 publications
8
63
2
1
Order By: Relevance
“…CYP2E1 activities are normally distributed in the general population; however, nonconformity has been observed in both domestic and overseas studies, due to apparent racial differences. Studies have shown that the WT genotype of tuberculosis patients of Han nationality in the case group was higher than that in the control group, which agrees with the results of Vuilleumier et al (2006), Lee et al (2010), and Wang et al (2010). A study conducted by Huang et al (2003) showed that risks of hepatic injury in individuals carrying the WT genotype were 2.38-fold higher than in those carrying mutant genes, while studies in Korea and Brazil showed no evidence of significant differences between patients with the WT and mutant gene (Cho et al, 2007;Teixeira et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…CYP2E1 activities are normally distributed in the general population; however, nonconformity has been observed in both domestic and overseas studies, due to apparent racial differences. Studies have shown that the WT genotype of tuberculosis patients of Han nationality in the case group was higher than that in the control group, which agrees with the results of Vuilleumier et al (2006), Lee et al (2010), and Wang et al (2010). A study conducted by Huang et al (2003) showed that risks of hepatic injury in individuals carrying the WT genotype were 2.38-fold higher than in those carrying mutant genes, while studies in Korea and Brazil showed no evidence of significant differences between patients with the WT and mutant gene (Cho et al, 2007;Teixeira et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…The GSTM1 gene is polymorphic in humans and has three known alleles: GSTM1*A, GSTM1*B and GSTM1O (null), which is the most common variant. The null variant results in undetectable expression of the gene product [70], leading to excessive accumulation of reactive oxygen species and consequently higher susceptibility to carcinogenic events due to DNA damage [71]. Three studies in Mexican and Brazilian populations evaluated the association between the null genotype and BC risk.…”
Section: Other Bc Susceptibility Mutations In Central and South Amerimentioning
confidence: 99%
“…On the other hand, it has been observed that GSTs play an important protective role in preventing the elevation of SGOT and SGPT in the liver, and it is speculated that people with null GSTM1 or GSTT1 genotypes might not detoxify toxic reactive metabolites efficiently and thus might have a higher risk of elevated levels of SGOT and SGPT in the liver (Xiang et al, 2014). Other studies have been inconsistent about the relationship between the null GSTM1 and GSTT1 genotypes and high levels of SGOT and SGPT liver enzymes (Wang et al, 2010;Xiang et al, 2014). A plausible biological explanation for the protective association observed in this study might be that elevated glucose levels mimic the protective association of SGOT observed in patients with BC in this study.…”
Section: Discussionmentioning
confidence: 98%
“…This leads to a lack of expression of the GST mu enzymes that results in decreased antioxidant activity in the cell (Duggan et al, 2013), high accumulation of reactive oxygen species (ROS), and consequently higher susceptibility to carcinogenic events due to DNA damage (McLellan et al, 1997;Wang et al, 2010). It has been suggested that the null GSTM1 is associated with an increased risk of developing some types of cancers including BC (McLellan et al, 1997;de Aguiar et al, 2012;Duggan et al, 2013;Possuelo et al, 2013;Wan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%